Saguling Empowerment Program: Community-Based Organic Waste Management Best Practices as an Effort to Preserve the Saguling Reservoir by PT PLN Indonesia Power UBP Saguling - Salsabila, Alfira; Sofiyah; Kurniawan, Taufan; Ghulam S, Muhammad Rio; Yohana, Eva (Global Writing Academica Researching & Publishing, 2025)
Waste management, especially organic waste, remains a significant challenge in the Greater Bandung area. This study aims to analyze the role of community-based waste management in reducing organic waste generation at the Sarimukti landfill and its impact on the lifespan of the Saguling Reservoir. The research method involved analyzing primary and secondary data, including the amount of organic waste generated, the quantity of chicken feed produced from maggot processing, chicken farmers' income, and electricity production at Saguling Reservoir. Primary data were obtained from surveys of 26 Waste Bank Units throughout Greater Bandung and PT PLN Indonesia Power UBP Saguling, which initiated the Saguling Berdaya program. The results showed that the program successfully managed community organic waste using the maggot bioconversion method from 2023 to July 2025, achieving a total of 887.03 tons, with an average of 28.61 tons/month converted into layer chicken feed. The production of 50 kg/day of fresh maggots was used to feed 1,200 laying hens, which produced 62 kg of eggs/day. In 2024, PT. PLN IP UBP Saguling successfully collected 660.48 tons of organic waste. This result contributed to reducing the organic waste load at the Sarimukti landfill by 0.09% of the total organic waste, which was 724,598 tons. This implementation had a significant economic impact, as farmers were able to save Rp122,148,000.00 per month in feed costs. From an environmental perspective, organic waste processing contributes to a reduction in sedimentation at the Saguling Reservoir by 0.11-0.50%. This reduction in sedimentation has a direct impact on extending the life of the reservoir and enhancing the efficiency of electricity production, resulting in economic benefits of IDR 115,027,450 in 2023, IDR 247,713,748 in 2024, and IDR 183,338,955 in 2025. Thus, community-based organic waste management through the Saguling Berdaya Program not only supports environmental sustainability but also strengthens food security and provides economic benefits for the surrounding community.